2007
DOI: 10.1016/j.ultsonch.2006.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-induced concurrent ultrasonic degradation of volatile and non-volatile aromatic compounds

Abstract: Acoustic cavitation, induced by ultrasound, can be used to eliminate organic pollutants from water. This type of ultrasonic treatment of polluted water can be grouped with those generally referred to as advanced oxidative processes since it involves hydroxyl radicals. In this case these highly active species are generated from the dissociation of water and oxygen dissociation caused by cavitation bubble collapse. The cavitation induced degradation rates of organic compounds in water are mainly linked to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(48 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…These findings are consistent with those of Méndez-Arriaga et al (2008) which showed that the introduction of air promoted the formation of hydroxyl radical, thus contributing to the degradation of ibruprofen. Moreover, previous studies by Pétrier et al (2007), Torres et al (2008) and Chiha et al (2011) have also noted the importance of gas saturation on the sonochemical treatment of pollutants in water. In this experiment, the reaction medium became slightly acidic as the pH changed from 6 ± 0.3 to 4 ± 0.3, resulting to the generation of nitrate, nitrite and hydroxyl radicals as shown in Eqs.…”
Section: Effect Of Air Spargingmentioning
confidence: 88%
See 2 more Smart Citations
“…These findings are consistent with those of Méndez-Arriaga et al (2008) which showed that the introduction of air promoted the formation of hydroxyl radical, thus contributing to the degradation of ibruprofen. Moreover, previous studies by Pétrier et al (2007), Torres et al (2008) and Chiha et al (2011) have also noted the importance of gas saturation on the sonochemical treatment of pollutants in water. In this experiment, the reaction medium became slightly acidic as the pH changed from 6 ± 0.3 to 4 ± 0.3, resulting to the generation of nitrate, nitrite and hydroxyl radicals as shown in Eqs.…”
Section: Effect Of Air Spargingmentioning
confidence: 88%
“…Sonochemical degradation of organic pollutants in aqueous solutions is affected by air or gas bubbling (Pétrier et al 2007;Chiha et al 2011). To investigate the effects of this on the sonochemical degradation of E2 and EE2, continuous injection of air at equivalent flow rates was monitored during the sonication process.…”
Section: Effect Of Air Spargingmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, when US treatment was applied in a fruit smoothie at different amplitude levels (24.4-61 µm) and processing times (3-10 min), it was observed that the total phenolic content decreased with the increase of amplitude levels [68]. These degradation trends during US processing may be related to the formation of free radicals that occur during sonication, resulting in a potential development of different oxidation pathways [77]. When Carbonell-Capella et al [72] compared the effects of HIPEF and US processing on phenolic compounds of a mango-papaya blended beverage, they reported that the concentration of these compounds after HIPEF processing was significantly higher than those of untreated samples.…”
Section: Application Of Non-thermal Technologies In Fruit-based Bevermentioning
confidence: 99%
“…The slight decrease in pasteurized juice could be due to the oxidation reactions of ascorbic acid caused by the temperature below boiling point (72°C pasteurization). While the loss of ascorbic acid during sonication process might be by oxidative processes in aerobic and anaerobic environments associated with the production and use of hydroxyl radicals [16,17].…”
Section: Effect Of the Thermoultrasound And Pasteurization On The Ascmentioning
confidence: 99%